Controlling local deformation in graphene using micrometric polymeric actuators. (25th September 2018) - Colangelo, F; Pitanti, A; Mišeikis, V; Coletti, C; Pingue, P; Pisignano, D; Beltram, F; Tredicucci, A; Roddaro, S
Abstract: Lattice deformation and electronic properties are closely linked in two-dimensional materials such as graphene. However, a fine control of the spatial strain distribution is crucial to correctly engineer the electrical properties of atomic-thick materials. Although several solutions have been proposed so far, the flexibility required to fully master and investigate arbitrary strain profiles remains challenging. Here, we locally deform graphene using the poly-methyl-methacrylate (PMMA) shrinkage induced by electron-beam irradiation. Arbitrary design of pulling geometries and different actuation magnitudes can be both defined in the PMMA by electron-beam patterning. Specific graphene strain fields can be obtained using reverse engineering of the PMMA micro-actuators geometry. As proof of principle of operation, we target and we successfully demonstrate a strongly localized and virtually-pure uniaxial strain profile. This configuration is promising for the implementation of the pseudo-magnetic field and allows identifying the graphene crystal orientation. Strain field characterization and out-of-plane graphene deformations are demonstrated and studied by Raman, scanning-electron and atomic-force microscopy. These can all be easily combined with the present device architecture. Remarkably, the induced strain in graphene can be released by heating the sample and reconfigured or restored again by re-irradiating the polymer. In situ observation of nano-mechanical evolution of devices show that micro-actuation can be strong enough to tear the graphene layer. As side result, the in situ failure visualization allows using our technique to qualitative estimate the mechanical quality of chemically synthetized graphene. The relative simplicity and flexibility of our method opens new opportunities for the investigation of straintronics, pseudo-magnetic field and nano-mechanics in two-dimensional materials.